2020
DOI: 10.1007/s10072-020-04546-8
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalography at the time of Covid-19 pandemic in Italy

Abstract: Objective During the Covid-19 pandemic, government restrictions limited health care to urgent needs. Neurophysiology centers had to suddenly reschedule their activities, with a lack of specific recommendations about electroencephalography (EEG) execution. During the pandemic phase 1, we launched an online survey to understand the flaws and strengths of the EEG management in Italy at the time of Covid-19 pandemic. Methods A 45-item online survey (published from April 16 to 30, 2020), endorsed by the Italian Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 10 publications
1
50
0
Order By: Relevance
“…EEG-related papers (Table 4): While change in mental status has frequently been reported in patients with COVID-19 [26,27,55,60,65,66,70], and while there are many reports on clinical and subclinical seizures and status epilepticus in these patients [33-47, 63, 66], EEG studies have been significantly ignored and underused in these patients globally. Three studies showed that EEG services have been significantly disrupted by the pandemic of COVID-19 [18,19,57]. Three other studies showed that many of the patients with COVID-19 and encephalopathy/seizures had epileptiform discharges/seizures in their EEG [29,54,55].…”
Section: Resultsmentioning
confidence: 99%
“…EEG-related papers (Table 4): While change in mental status has frequently been reported in patients with COVID-19 [26,27,55,60,65,66,70], and while there are many reports on clinical and subclinical seizures and status epilepticus in these patients [33-47, 63, 66], EEG studies have been significantly ignored and underused in these patients globally. Three studies showed that EEG services have been significantly disrupted by the pandemic of COVID-19 [18,19,57]. Three other studies showed that many of the patients with COVID-19 and encephalopathy/seizures had epileptiform discharges/seizures in their EEG [29,54,55].…”
Section: Resultsmentioning
confidence: 99%
“…An Italian study that surveyed people with and without epilepsy found that those with epilepsy reported a significantly increased risk of seizures and difficulties in obtaining follow-up clinic appointments. 15 …”
Section: Discussionmentioning
confidence: 99%
“…An Italian study that surveyed people with and without epilepsy found that those with epilepsy reported a significantly increased risk of seizures and difficulties in obtaining follow-up clinic appointments. 15 Shortage of ASM has not been a major concern during the current pandemic. Most respondents did not notice lack of availability of ASM, with the exception of long acting levetiracetam.…”
Section: Obtaining and Delivering Epilepsy Carementioning
confidence: 99%
“…Furthermore, there has been a drastic decrease in the number of procedures done during this pandemic [ 48 ]. The conduct of continuous EEG during this pandemic is limited to urgent cases only because of the safety concern imposed by the contagiousness of the virus and concerns to reduce the exposure to SARS-CoV-2 of EEG technicians during this pandemic.…”
Section: Discussionmentioning
confidence: 99%